Clinico-Etiological Profile of Cardiac Tamponade in a Tertiary Care Centre - HS Nataraj Setty; MC Yeriswamy; Santhosh Jadav; Soumya Patra; Kumar Swamy; Shivanand S Patil; KS Ravindranath; Veeresh Patil; CN Manjunath (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2016)
Background: Pericardial tamponade, a life-threatening condition caused by the accumulation of fluid in the pericardial sac, can be acute or chronic. Mortality and morbidity can be minimized on prompt diagnosis and treatment with percutaneous drainage. Materials and methods: 246 patients admitted with cardiac tamponade between Jan 2010 and Aug 2014 was enrolled in the study. After clinical examination and echocardiographic assessment, all the patients were subjected to emergency pericardiocentesis (both diagnostic and therapeutic). Three samples of the aspirate were sent for biochemical, serological, and cytological analysis. The data collected was then analyzed. Results: Tuberculosis is the commonest cause in our study. Post procedural and post-surgical causes are insignificant in numbers. Overall mortality rate in our study is 6% which is much lesser than other studies. Procedure related cardiac tamponade mortality rate was 6%. Conclusion: Initial assessment with clinical, serologic, and echocardiographic investigation and careful follow-up can in most cases yield a causal diagnosis. The prognosis depends chiefly upon the patient's underlying disease.